Diagnostic Accuracy of Point-of-Care Ultrasound Integrated into Clinical Examination for Acute Diverticulitis: A Prospective Multicenter Study - Nazerian, Peiman; Gigli, Chiara; Donnarumma, Emilia; de Curtis, Ersilia; Bribani, Andrea; Lanzi, Sabina; Rovida, Serena; Magazzini, Simone; Grifoni, Stefano; Perani, Cristiano (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose Diverticulitis is a common cause of abdominal pain and CT scan is commonly used for its diagnosis in the emergency department (ED). The diagnostic performance of point-of-care ultrasound (POCUS) integrated into a clinical exam for diverticulitis is still not established. We evaluate the accuracy of clinical-sonographic assessment for the diagnosis of diverticulitis and whether POCUS could improve the selection of patients needing CT scan for complicated diverticulitis.Materials and Methods This is a multicentric observational study involving adult patients suspected of having diverticulitis presenting at 4 EDs. 21 sonographer physicians were asked to diagnose diverticulitis and complicated diverticulitis based on clinical-sonographic assessment. The final diagnosis was established by two reviewers, blinded to POCUS, based on data collected during the one-month follow-up comprehensive CT scan.Results Among 393 enrolled patients, 218 (55.5 %) were diagnosed with diverticulitis and 33 (8 %) had complicated diverticulitis. The time to diagnosis by the sonographer physicians was shorter compared to standard care (97 ± 102 vs. 330 ± 319 minutes, p < 0.001). Clinical-sonographic assessment showed optimal sensitivity (92.7 %) and specificity (90.9 %) for diverticulitis. However, the sensitivity (50 %) for complicated diverticulitis was low. The sonographer physician would have proceeded to CT scan in 194 (49.4 %) patients and the CT scan request compared to the final diagnosis of complicated diverticulitis demonstrated 94 % sensitivity.Conclusion Clinical-sonographic assessment is rapid and accurate for the diagnosis of diverticulitis. Even if POCUS has low sensitivity for complicated diverticulitis, it can be used to safely select patients needing CT.
Keywords: abdominal pain; diagnosis; ultrasound; computed tomography; diverticulitis